Pengaruh Bimbingan Orang Tua Dan Minat Baca TerhadapPrestasi Belajar Pada Siswa Kelas Atas SDN Sambi 1 Tahun Ajaran 2015/2016 - Ernawati, Anis Budi, Drs. Mulyadi S. K., SH.,M.Pd (2016)
This study aims to determine: (1) the effect of parental guidance on learning achievement science in students up class SDN Sambi 1, (2) the effect of reading interest on learning achievement science in students up class SDN Sambi 1, (3) the effect of parental guidance and reading interest on learning achievement science in students up class SDN Sambi 1. This study included into the quantitative research. The study population was all students up class SDN Sambi 1 totalling 76 students. While the sample was 60 students. The technique of collecting data are using interview, documentation and questionnaires. Data were analyzed using t test and F test, that preceded by analysis prerequisite test is normality test and linearity test. The conclusion of this study are: (1) There is an effect of parental guidance toward science learning achievement in up class students on SDN Sambi 1. Based on t test known that t > t it is 2,048 > 1,671 and significance value < 0,05, it is 0,045. (2) There is an effect of reading interest towards science learning achievement in up class students on SDN Sambi 1. based on t test known that t table count > t it is 2,117 > 1,671 and signivicance value < 0,05, it is 0,038. (3) There is the effect of parental guidance and reading interest toward science learning achievement in up class students on SDN Sambi 1. based on F test known that F count table, > 3,15 and signivicance value < 0,05, it is 0,003. Key words: parental guidance, reading interest, and learning achievement